The vascular response to ultrathin biodegradable polymer sirolimus-eluting stent at 2-weeks and 1-year follow up in patients with ST-elevation myocardial infarction. (3rd October 2022) - Oishi, Y; Tsujita, H; Arai, T; Sakai, R; Sato, S; Tanaka, H; Ogura, K; Masaki, R; Kondo, S; Tsukamoto, S; Higuchi, S; Sumida, A; et al.
Abstract: Background: Recent clinical study suggests newer-generation drug-eluting stents (DES) that combine ultrathin strut and nano-coating with biodegradable polymers sirolimus-eluting stent (BP-SES) could improve long-term clinical outcomes in patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI) over current generation DES. However, the details of vascular response in very early and chronic phase have not been systematically addressed. Objective and method: We exploratory investigate early and chronic vascular response following BP-SES implantation in patients with STEMI to reveal mechanism of the favorable clinical outcomes in recent studies using frequency domain-optical coherence tomography (FD-OCT). Consecutive twenty-four patients with STEMI who underwent FD-OCT after primary PCI and were eligible for follow-up FD-OCT at 2 weeks and 1 year after implantation were enrolled between June 2018 and August 2020. OCT was performed immediately after PCI, at 2-weeks (2W) and 1-year (1Y) after the primary PCI. Struts were recorded as uncovered if any part was visibly exposed in the lumen or covered if a layer of tissue covered all reflecting surfaces. Struts of stents that are smaller than 3.0mm of diameter with more than 80μm between the center reflection and the adjacent vessel surface were recorded as malapposed. The reduction of atherothrombotic protrusion burden within the stent was also assessed. Results: Twenty-four patients (age 64.9±11.4 years, male 83.3%) were enrolled. The percentage of uncovered struts significantly decreased from post-PCI to 2W follow-up and from 2W follow-up to 1Y follow-up (62±20% post-PCI versus 27±11% at 2W follow up, p<0.0001 and 2W follow-up versus 3.3±3.3% at 1Y follow up, p<0.0001). Malapposed struts also decreased from post-PCI to 2W follow-up (4.1±3.6% post-PCI versus 1.5±2.2% at 2W follow-up, p<0.0001), but no significant difference was shown between 2W follow-up and 1Y follow-up (2W follow-up versus 1.0±2.3 at 1Y follow up, p=0.12). The average protrusion area of athero-thrombotic burden decreased (0.57±0.32 at post-PCI versus 0.42±0.22 mm 2 at 2W follow up, p<0.0001) and its volume showed similar tendency (16.6±10.7 at post-PCI versus 12.9±8.23 mm 3 at 2W follow up, p=0.0011). Thrombus was shown in all patients at post-PCI, but two patients (8.0%) showed it at 1Y follow-up. Conclusion(s): This study elucidated very early and chronic vascular responses following ultrathin strut BP-SES implantation in STEMI patients by FD-OCT. It showed resolution of athero-thrombotic materials in very early phase and favorable progression of strut coverage in very early and chronic phase. Funding Acknowledgement: Type of funding sources: None.